Seismic microzonation of the historic peninsula of Istanbul - Ince, Goekce Cicek; Yildirim, Mustafa; Ozaydin, Kutay; Ozener, Pelin Tohumcu (SPRINGER HEIDELBERG, 2008)
In this study, the geological and geotechnical conditions of old Istanbul (Fatih and Eminonu provinces) were investigated in detail and a seismic microzonation study was undertaken for this historical peninsula, which is the site of many ancient structures. Dynamic site response, liquefaction potential and slope stability analyses were carried out, based on field and laboratory tests and earthquake time histories computed with respect to probabilities of exceedance of 10 and 40% in 50 years. The output data obtained from the analyses were evaluated by GIS techniques, and ground shaking, liquefaction susceptibility and landslide hazard maps were prepared.
Keywords: microzonation; liquefaction; landslide hazard; dynamic site response analysis; amplification; earthquake simulation; Engineering; Geology